Isolation and Characterization of ScGluD2, a New Sugarcane beta-1,3-Glucanase D Family Gene Induced by Sporisorium scitamineum, ABA, H2O2, NaCl, and CdCl2 Stresses - Su, Yachun; Wang, Zhuqing; Liu, Feng; Li, Zhu; Peng, Qiong; Guo, Jinlong; Xu, Liping; Que, Youxiong (Frontiers in Plant Science, 2016)
Beta-1,3-glucanases (EC 3.2.1.39), commonly known as pathogenesis-related (PR) proteins, play an important role not only in plant defense against fungal pathogens but also in plant physiological and developmental processes. However, only a limited number of sugarcane beta-1,3-glucanase genes have been isolated. In the present study, we identified and characterized a new beta-1,3-glucanase gene ScGluD2 (GenBank Acc No. KF664181) from sugarcane. An X8 domain was present at the C terminal region of ScGluD2, suggesting beta-1,3-glucan-binding function. Phylogenetic analysis showed that the predicted ScGluD2 protein was classified into subfamily D beta-1,3-glucanase. Localization of the ScGluD2 protein in the plasma membrane was determined by tagging it with green fluorescent protein. The expression of ScGluD2 was more up-regulated in sugarcane smut-resistant cultivars in the early stage (1 d or 3 d) than in the susceptible ones after being challenged by the smut pathogen, revealing that ScGluD2 may be involved in defense against the invasion of Sporisorium scitamineum. Transient overexpression of ScGluD2 in Nicotiana benthamiana leaves induced a defense response and exhibited antimicrobial action on the tobacco pathogens Pseudomonas solanacearum and Botrytis cinerea, further demonstrating that ScGluD2 was related to the resistance to plant pathogens. However, the transcripts of ScGluD2 partially increased (12 h) under NaCl stress, and were steadily up-regulated from 6 h to 24 h upon ABA, H2O2, and CdCl2 treatments, suggesting that ABA may be a signal molecule regulating oxidative stress and play a role in the salt and heavy metal stress-induced stimulation of ScGluD2 transcripts. Taken together, ScGluD2, a novel member of subfamily D beta-1,3-glucanase, was a stress-related gene of sugarcane involved in plant defense against smut pathogen attack and salt and heavy metal stresses.